SIMULATION OF RADIO FREQUENCY IDENTIFICATION BASED LIBRARY MANAGEMENT SYSTEM - Saleh Hassan, Abbas; Talal Hussein, Raoof (Journal of Engineering and Sustainable Development, 2017)
(RFID) is a technology used for identification or tracking of any objects. RFID system contains "tag and RFID reader" that performs the main operation of identifying things. a library system has been built using RFID components and using special programs. Microsoft access database was used to build the tables that needs to store the information of the books. The implementation of the system has been done in two main stages, the first one is a Hardware Device "RFID-RC522" and "Arduino card", and the second is the implementation of a specific read software program, a graphical User Interface (GUI) for the system has been built by using Visual Basic (VB).